ALTERNATIVE WAYS TO RESOLVE CRIMINAL LEGAL CONFLICTS - Sysak, Vladyslav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: the goal is to comprehensively investigate the theoretical and practical aspects of applying alternative methods to resolve criminal legal conflicts in Ukraine. Research methods: the research employs logical-legal, formal-legal, cognitive-analytical, comparative-legal analysis, deduction, and other methods. Results: the study proposes a correlation between traditional methods of resolving criminal legal conflicts and alternative methods. The essence of criminal legal conflicts and the application of existing legislation in this aspect are analyzed. Discussion: contemporary concepts of the term «criminal legal conflict» are examined. The possibilities of applying alternative methods to resolve criminal legal conflicts are analyzed in accordance with current legislation. In modern society, there is a need to consider and implement alternative methods for resolving criminal legal conflicts, driven by the contemporary societal demand for the application of adaptive and flexible conflict resolution methods that take into account the interests of all parties and contribute to the restoration of justice. Traditional methods lead to the burdening of the judicial system, prolonged processes, and do not always satisfy the needs of all parties. Research into alternative methods for resolving criminal legal conflicts is a current task aimed at ensuring the efficiency of justice and meeting society’s demand for fairness. Traditional methods of resolving criminal legal conflicts are based on pre-trial investigation and the punishment of those found guilty by the court. The existing system has its limitations and drawbacks. For instance, the concentration of criminal justice on punishing the offender often results in the victim practically being left out of the resolution of the criminal legal conflict, losing the right to participate in their own case. The punitive focus of the criminal process is directly linked to the interpretation of a criminal offense as a violation of the state’s laws rather than causing harm to specific individuals and their relationships. In turn, victims endure a double physical, moral, and material burden: firstly, directly from the criminal offense, and secondly, from the established method of justice, which does not allow for a comprehensive resolution of their problems and timely and adequately addressing their concerns.